Предмет: Алгебра,
автор: Аноним
Упростить сначала,а потом подставить.
(a-4)²+(a-4) (a+4)+8a при a=0,3
Ответы
Автор ответа:
1
(а-4)²+(а-4)(а+4)+8а; при а =0,3
а²-8а+16+а²-16+8а=2а²=2×0,3²=2×0,09=0,18
а²-8а+16+а²-16+8а=2а²=2×0,3²=2×0,09=0,18
Аноним:
Спасибо большое!
Автор ответа:
1
Yes вот пожалуйста легко и просто
Приложения:
Похожие вопросы
Предмет: Биология,
автор: vitalinamartynik
Предмет: Математика,
автор: fannigame06
Предмет: Геометрия,
автор: makcimkakakaka
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: darina123007